2020
DOI: 10.1017/s0022029920000710
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofINSIG1on the milk fat synthesis of buffalo mammary epithelial cells

Abstract: We hypothesized that insulin-induced gene 1 (INSIG1) affects milk fat synthesis in buffalo. For this reason, the protein abundance of INSIG1 in the mammary tissue of buffalo during the peak period of lactation and dry-off period was evaluated. The results showed that the expression of INSIG1 at the peak of lactation was lower than that in the dry-off period. To explore the role of INSIG1 in milk fat synthesis, the buffalo mammary epithelial cells (BMECs) were isolated and purified from buffalo mammary tissue, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The BuMECs were obtained from five buffalo in lactation (60 days postpartum) as previously reported by our group (Fan et al, 2020). Briefly, the buffalo mammary tissues were stripped of connective tissues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BuMECs were obtained from five buffalo in lactation (60 days postpartum) as previously reported by our group (Fan et al, 2020). Briefly, the buffalo mammary tissues were stripped of connective tissues.…”
Section: Methodsmentioning
confidence: 99%
“…The process for generation and transduction was performed as previously reported (Fan et al, 2020). Briefly, the 239 T cells were, respectively, transfected with pLVX‐ELOVL6‐IRES‐ZsGreen1 and pLVX‐IRES‐ZsGreen1 vector (Lv‐GFP) for packaging lentiviral particles.…”
Section: Methodsmentioning
confidence: 99%
“…Insulin inducible genes INSIG1 and INSIG2 are located in endoplasmic reticulum and play an important role in regulating lipid metabolism ( 75 ). The mRNA abundance of INSIG1 in breast tissue during peak lactation period was lower than that in dry period, which reveal the potential importance of INSIG in milk fat metabolism ( 76 ). After overexpression INSIG1 or INSIG2 in GMECs, the expression of ACACA and FASN was down-regulated, the content of TAG and total cholesterol (TC) were decreased.…”
Section: Negative Regulation Of De Novo Synthesis Of Famentioning
confidence: 99%
“…Previous studies have shown that INSIG1 can effectively block the proteolysis activation of SREBP family members ( 114 ) and play an important role in de novo milk fat synthesis in ruminants ( 50 ). Fan et al ( 76 ) measured the protein abundance of INSIG1 in the mammary gland of buffalo during peak lactation and dry period, and found that the expression of INSIG1 in the peak lactation period was lower than that in the dry period, and the overexpression INSIG1 significantly decreased the expression of GPAM and AGPAT6. The opposite result was obtained after INSIG1 was knockout, which was also confirmed by Li et al ( 77 ).…”
Section: Tag Synthesismentioning
confidence: 99%
See 1 more Smart Citation